Free radical scavenging effect of phyllanthus simplex: In vitro and in vivo study - Kumar S.; Sachdeva N.; Amir M.; Kumar A.; Singh S.K. (My University, 2025)
The ethanolic extract of Phyllanthus simplex (Euphorbiaceae) was found to contain free and conjugated phenolic compounds and was therefore screened for anti-oxidant activity using in vitro and in vivo experimental models. The extract exhibited a high degree of inhibition on rat brain lipid peroxidation up to 92.01 ± 0.002% by in vitro method. P. simplex extract also exhibited dose dependent inhibitory effects on lipid peroxidation up to the concentration of 18.7 μg/ml of brain tissue. In vivo studies using albino rats showed that the plant extract (100mg extract/kg, p.o.) significantly antagonized CCl 4 (0.5 ml/kg, p.o.) induced increase in malondialdehyde. The in vivo anti-oxidant activity of P. simplex was found to be comparable to that of Vitamin-E (50mg/kg, p.o.), used as standard.